Impact of IUCEE IGIP Engineering Educator’s Certification Program on Teaching Performance of Participants - Kavade, Mukund V.; Khot, Sachin B.; Telsang, Martand T. (Journal of Engineering Education Transformations, 2017)
Mushrooming growth of engineering institutes in India has increased the demand for qualified and competent teachers in engineering education.Minimum eligibility for entry level Assistant Professor is post graduation in the concerned or equivalent engineering discipline. No formal education or training in the field of engineering education is mandatory. Comprehensive training programin engineering educationwas not available in India. Indo US Collaboration for Engineering Education (IUCEE), USAin collaboration with IGIP, Austria has recently launched a program that is fully customized for the engineering educators in India. First author of this paper has successfully completed this program. Student’ feedback on the teaching performance of the author, before and after undergoing this program is compared. It is observed that teacher training program has improved the teaching performance of the authors.